Effect of Special Exercises in the Development of Special Endurance (Endurance Strength and Speed Endurance) for the Effectiveness of Running 400 Meters Class (CP 36) - Hind Walid Kalaf (Journal of Global Pharma Technology, 2018)
The sport of the disabled is one of the most important sports that have witnessed remarkable development in recent years, especially after the London Paralympic Games 2012, especially on athletics. In view of the close relationship between modern training theories and its practical, scientific and training aspects to achieve the best levels, Athletes in category (CP 36) The researcher noted the lack of interest in this category of training, which depends on the scientific basis in terms of physical tests that fit the possibilities and capabilities of the category (CP 36).Where the objectives of the research were determined:Prepare special exercises in the development of your endurance.Identify the impact of special exercises in developing the endurance force for an effective 400 meters.Identify the effect of special exercises in the development of endurance speed for the effectiveness of 400 meters for class (CP 36).Research HypothesesThere were statistically significant differences between the pre and posttests of the two experimental groups in carrying power for the effectiveness of running 400 meters.There were statistically significant differences between the post-test of the two experimental groups in carrying the speed of running 400 meters for the class (CP36).The researcher used the experimental approach to suit the nature of the research with two equal groups.The research community was selected from the elite players (ages 18-23) category (CP 36) with a running efficiency of 400 m. The number of players (10) was divided into two experimental groups randomly and with (5) players for each group.The Researcher ConcludedThe special exercises showed a clear development in the endurance of disabled players in the category of CP 36)The wide development was the result of the prevailing quality of the effectiveness of the speed of 400 meters.Keywords: Special exercises, Special endurance, Endurance strength and speed endurance.